Discrete and continuous model of three-phase linear induction motors considering attraction force and end-effects - Nicolás Toro-García; Yeison Alberto Garcés-Gómez; Fredy E. Hoyos (Institute of Advanced Engineering and Science, 2020)
The continuous model of the linear induction motor (LIM) has been made considering the edge effects and the attraction force. Taking the attraction force into account is im- portant when considering dynamic analysis when the motor operates under mechanical load. A laboratory prototype has been implemented from which the parameters of the equivalent LIM circuit have been obtained. The discrete model has been developed to quickly obtain computational solutions and to analyze non-linear behaviors through the application of discrete control systems. In order to obtain the discrete model of the LIM we have started from the solution of the continuous model. To develop the model, the magnetizing inductance has been considered, which reflects the edge effects. In the results, the model is compared without considering the edge effects or the attraction force with the proposed model.